-5x+3=26+4

Simple and best practice solution for -5x+3=26+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+3=26+4 equation:


Simplifying
-5x + 3 = 26 + 4

Reorder the terms:
3 + -5x = 26 + 4

Combine like terms: 26 + 4 = 30
3 + -5x = 30

Solving
3 + -5x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -5x = 30 + -3

Combine like terms: 3 + -3 = 0
0 + -5x = 30 + -3
-5x = 30 + -3

Combine like terms: 30 + -3 = 27
-5x = 27

Divide each side by '-5'.
x = -5.4

Simplifying
x = -5.4

See similar equations:

| (32+x)-10=3x | | 50=5000/12*r | | 2=14-2h | | (-2+3a)/(9a^2-4) | | 4x-x+5=3x-9 | | 10x+90=100 | | 95=6000/12*r | | 4=31-9t | | 6(x+2)=2(3x+2)+8 | | 0.4(2-x)-(x+3)= | | 7x/3/8=6x-5/8 | | t+1/2=2t-3/6 | | 2=56-9t | | -35+4/15 | | 13x+30=23x-15 | | 0.35s+0.6(30-s)=0.45(30) | | 26-9x=3x-1 | | 9-6x/7=16 | | 12(3x+3)-7(2x-6)=2x-42 | | 6-3x-5x-10x+18-12= | | p-16=51 | | -7/2*10 | | 2(5x-3)-2x-4=5-(6x+1) | | -9-6x/7=16 | | 0.20x+0.05(10-x)=0.10(14) | | -27=n-20 | | 14-3(x-2)=x+16 | | 2a+7=50 | | -7/2-1/4 | | -7/10t=1/8 | | (43-7x)+(83-11x)=(117-22x) | | x^2-12x-16=0 |

Equations solver categories